Reactive Oxygen Species-Dependent Nitric Oxide Production Contributes to Hydrogen-Promoted Stomatal Closure in Arabidopsis - Xie, Yanjie (American Society of Plant Biologists, 2014)
The signaling role of hydrogen gas (H(2)) has attracted increasing attention from animals to plants. However, the physiological significance and molecular mechanism of H(2) in drought tolerance are still largely unexplored. In this article, we report that abscisic acid (ABA) induced stomatal closure in Arabidopsis (Arabidopsis thaliana) by triggering intracellular signaling events involving H(2), reactive oxygen species (ROS), nitric oxide (NO), and the guard cell outward-rectifying K(+) channel (GORK). ABA elicited a rapid and sustained H(2) release and production in Arabidopsis. Exogenous hydrogen-rich water (HRW) effectively led to an increase of intracellular H(2) production, a reduction in the stomatal aperture, and enhanced drought tolerance. Subsequent results revealed that HRW stimulated significant inductions of NO and ROS synthesis associated with stomatal closure in the wild type, which were individually abolished in the nitric reductase mutant nitrate reductase1/2 (nia1/2) or the NADPH oxidase-deficient mutant rbohF (for respiratory burst oxidase homolog). Furthermore, we demonstrate that the HRW-promoted NO generation is dependent on ROS production. The rbohF mutant had impaired NO synthesis and stomatal closure in response to HRW, while these changes were rescued by exogenous application of NO. In addition, both HRW and hydrogen peroxide failed to induce NO production or stomatal closure in the nia1/2 mutant, while HRW-promoted ROS accumulation was not impaired. In the GORK-null mutant, stomatal closure induced by ABA, HRW, NO, or hydrogen peroxide was partially suppressed. Together, these results define a main branch of H(2)-regulated stomatal movement involved in the ABA signaling cascade in which RbohF-dependent ROS and nitric reductase-associated NO production, and subsequent GORK activation, were causally involved.